el-Berîkatü’l-Mahmûdiyye fî şerhi’t-Tarîkati’l-Muhammediyye ve’ş-şerîʿati’n-nebeviyye fi’s-sîreti’l-Ahmediyye - 880-01 Hâdimî, Ebû Saîd, 1701-1762. (İstanbul İstanbul)
2 cilt 1 ciltte (3. cilt 371 sayfa, 4. cilt 230 sayfa)